Flexible Data Refreshing Architecture for Health Information System Integration - Kermanshahani, Shokooh; Hamidi, Hamid Reza (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2023)
Background: Having a consistent and unified view of heterogeneous distributed medical information sources is an inevitable need of health informatics. Integrating medical information of patients or about a disease, a treatment or side effects of a drug, etc, is very useful to help medical education, to achieve medical research goals and to provide the computer- based decision support systems. Contribution: This article proposes a flexible incremental update method for the materialized part of the integration system. It permits us to manage the integration system according to the characteristics of the data sources which can change. Method: This paper presents a hybrid data integration approach in which the materialized part of the system in mediator is the object indexation structure based on an instance classification of the sources objects which correspond to the global schema. The object identifier of each object in the indexation structure is materialized together with the attributes which are needed for the incremental updating of this indexation (classifying attributes). Results: The main idea of this paper is to develop a hybrid data integration framework, which represents a new aspect of a hybrid method focusing on flexible data refreshing. Conclusion: This hybrid approach implements a vertical hybrid approach. It means that at the mediator level, some data of each object are materialized and others are virtual.